EFFECTIVENESS OF CROSS-SECTORAL CERTIFICATE REGISTRATION SERVICES AT THE NATIONAL LAND AGENCY (BPN) OF TASIKMALAYA REGENCY - Roza Milasari; Sri Astuti Pratminingsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of public policy and organizational communication on employee work effectiveness in the implementation of the Cross-Sector Land Certificate Registration Program in Tasikmalaya Regency. The approach used is a descriptive verification method with a quantitative approach. Data collection techniques were carried out through questionnaires distributed to employees of the ATR/BPN, the Department of Agriculture, Food Security, and Fisheries (DPKPP), and village officials involved in the program. Data analysis used multiple linear regression to test the simultaneous and partial effects between variables. The results of the study indicate that public policy and organizational communication have a significant simultaneous and partial effect on employee work effectiveness. Clear and structured policies and effective internal communication can accelerate the service process, strengthen coordination, and minimize miscommunication between implementing agencies. These findings confirm that the synergy between adaptively designed policies and a targeted organizational communication system is a key factor in improving the quality of public services in the land sector. This study also provides managerial implications that public sector management needs to strengthen cross-sector coordination and communication strategies to achieve efficient, accountable, and sustainable services.